The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1177/039139880703001007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Desferrioxamine (DFO) for Removal of Thallium Ions in Rat

Abstract: An investigation was conducted to evaluate the ability of DFO following the administration of thallium salt in male Wistar rats. Thallium was introduced to several groups of weanling male Wistar rats via different means, through drink, food and intraperitoneal injection. A control group was fed on a diet containing a normal level of iron. After a period of 30 days, all the rats administered thallium were severely anemic and showed toxicity symptoms through loss of hair, an increase in thallium and a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…The reason for this important observation is that deferiprone is able to redistribute iron in mammals (Evans et al 2012). In comparison to the results obtained by Fatemi et al (2007, 2009, Tubafard and Fatemi (2008) it can be also concluded that the two chelators (deferasirox ? deferiprone) are more efficient as combined therapy than single therapy in removing chromium from rat organs.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The reason for this important observation is that deferiprone is able to redistribute iron in mammals (Evans et al 2012). In comparison to the results obtained by Fatemi et al (2007, 2009, Tubafard and Fatemi (2008) it can be also concluded that the two chelators (deferasirox ? deferiprone) are more efficient as combined therapy than single therapy in removing chromium from rat organs.…”
Section: Discussionmentioning
confidence: 81%
“…This kind of therapy by combining two chelators is based on the assumption that various chelating agents mobilize toxic elements from different tissue compartments and therefore better results are expected (Flora et al 1995). Results of this kind of combined chelation therapy have been confirmed by Amiri et al (2007), Fatemi et al (2007Fatemi et al ( , 2009), Tubafard and Fatemi (2008). The aim of the present research was to test the chelation potency of deferasirox and deferiprone in combination, given to animals after chromium loading.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is obvious that the cadmium concentration after chelation therapy was significantly decreased (P < 0.05). To investigate the effect of passing time in removing cadmium from the body spontaneously, one group was treated without chelation therapy (Fatemi et al 2007(Fatemi et al , 2009Tubafard and Fatemi 2008;Tubafard et al 2010). Elimination of cadmium by the biological system in the groups without the chelation therapy is not noticeable (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical evaluations of some chelators for removal of toxic metal ions in rats have been previously reported by (Fatemi et al 2007(Fatemi et al , 2009Tubafard and Fatemi 2008;Tubafard et al 2010). Chelation therapy is one of the most effective ways to remove toxic elements from the biological system.…”
Section: Discussionmentioning
confidence: 99%